Molecular characterization of tea mosquito bug from tea growing regions of India. (2nd September 2016) - Suganthi, M.; Chandrashekara, K. N.; Arvinth, S.; Raj Kumar, R.
Abstract: The tea mosquito bug, Helopeltis (Hemiptera: Miridae), is an insidious pest that poses a significant economical threat to tea plantations. As a basic first step to control this pest is authentic identification, but the inability to determine morphological characters of Helopeltis species makes this process very difficult. DNA barcoding is a reliable alternative to traditional morphological identification of this pest. Since tea is cultivated in different parts of the country, an attempt was made to molecular characterization of Helopeltis . This is the first report on molecular identification and diversity characterization of Helopeltis collected from tea growing regions of southern and north India, using cytochrome c oxidase subunit I ( COI ) gene of mitochondrial (mt) DNA. Beginning with the molecular identification of this pest is essential to start an effective pest management strategy, and will provide basic information for diffusion pattern, population dynamics and chemical application.